(Sprach-)Tests in der Praxis: Die Studie „Development Of North Rhine-Westphalian CLIL Students“ (DENOCS). - Rumlich, Dominik (Fremdsprachenunterricht empirisch erforschen. Grundlagen - Methoden - Anwendung)

Victorian Values in Nineteenth- and Twenty-First-Century Advertising and Consumer Practices - Strauß, Sara (anglistik & englischunterricht)

Facets of Children’s Fears in Twentieth- and Twenty-First-Century Stream-of-Consciousness Fiction - Strauß, Sara (Who’s afraid of...? Facets of Fear in Anglophone Literature and Film)

Constructions of ‘Otherness’ in Frances Hodgson Burnett’s The Secret Garden - Strauß, Sara (A Hundred Years of The Secret Garden – Frances Hodgson Burnett’s Children’s Classic Revisited)

The Persistence of Modernism in Light (Critical Engagements: A Journal of Criticism and Theory: Special Section: Eva Figes)

Der Zauber Magischer Welten - Flotmann, Christina
Interview 11 Oct. 2012

Spatial Representations of British Identities

A Bricolage of Identities in Crisis. Colour Photography Documenting Northern England under Thatcher - Tönnies, Merle (Facteurs d'Identité / Faktoren der Identität)

Polite Conversation, Implicatures, and Comical Effect: Jonathan Swift and P. G. Wodehouse - Mildorf, Jarmila (Imaginary Dialogues in English: Explorations of a Literary Form)

New Perspectives on Imaginary Dialogues: An Interdisciplinary Dialogue - Kinzel, Till; Mildorf, Jarmila (Imaginary Dialogues in English: Explorations of a Literary Form)

Second-Person Narration in Literary and Conversational Storytelling - Mildorf, Jarmila (Storyworlds)

Imaginary Dialogues in English: Explorations of a Literary Form

Mobility in Literature and Culture, 1500-1900

A Social Media Customer Service - Geierhos, Michaela; Lee, Yeong Su; Schuster, Jörg; Kobothanassi, Despina; Bargel, Matthias (Proceedings of the 22nd ACM Conference on Hypertext and Hypermedia)

SCM - A Simple, Modular and Flexible Customer Interaction Management System - Schuster, Jörg; Lee, Yeong Su; Kobothanassi, Despina; Bargel, Matthias; Geierhos, Michaela (International Conference on Information Society (i-Society 2011))
SCM is a simple, modular and flexible system for web monitoring and customer interaction management. In our view, its main advantages are the following: It is completely web based. It combines all technologies, data, software agents and human agents involved in the monitoring and customer interaction process. It can be used for messages written in any natural language. Although the prototype of SCM is designed for classifying and processing messages about mobile-phone related problems in social networks, SCM can easily be adapted to other text types such as discussion board posts, blogs or emails. Unlike comparable systems, SCM uses linguistic technologies to classify messages and recognize paraphrases of product names. For two reasons, product name paraphrasing plays a major role in SCM: First, product names typically have many, sometimes hundreds or thousands of intralingual paraphrases. Secondly, product names have interlingual paraphrases: The same products are often called or spelt differently in different countries and/or languages. By mapping product name variants to an international canonical form, SCM allows for answering questions like Which statements are made about this mobile phone in which languages/in which social networks/in which countries/...? The SCM product name paraphrasing engine is designed in such a way that standard variants are assigned automatically, regular variants are assigned semiautomatically and idiosyncratic variants can be added manually. With this and similar features we try to realize our philosophy of simplicity, modularity and flexibility: Whatever can be done automatically is done automatically. But manual intervention is always possible and easy and it does not conflict in any way with the automatic functions of SCM.
Keywords: Social Media Business Integration; Contact Center Application Support; Monitoring Social Conversations; Social Customer Interaction Management; Monitoring; Software Agents

Buy, Sell, or Hold? Information Extraction from Stock Analyst Reports - Lee, Yeong Su; Geierhos, Michaela (Modeling and Using Context: 7th International and Interdisciplinary Conference, CONTEXT 2011, Karlsruhe, Germany, September 26-30, 2011, Proceedings)
This paper presents a novel linguistic information extraction approach exploiting analysts’ stock ratings for statistical decision making. Over a period of one year, we gathered German stock analyst reports in order to determine market trends. Our goal is to provide business statistics over time to illustrate market trends for a user-selected company. We therefore recognize named entities within the very short stock analyst reports such as organization names (e.g. BASF, BMW, Ericsson), analyst houses (e.g. Gartner, Citigroup, Goldman Sachs), ratings (e.g. buy, sell, hold, underperform, recommended list) and price estimations by using lexicalized finite-state graphs, so-called local grammars. Then, company names and their acronyms respectively have to be cross-checked against data the analysts provide. Finally, all extracted values are compared and presented into charts with different views depending on the evaluation criteria (e.g. by time line). Thanks to this approach it will be easier and even more comfortable in the future to pay attention to analysts’ buy/sell signals without reading all their reports.

Processing Multilingual Customer Contacts via Social Media - Geierhos, Michaela; Lee, Yeong Su; Bargel, Matthias (Multilingual Resources, Multilingual Applications: Proceedings of the Conference of the German Society for Computational Linguistics and Language Technology (GSCL) 2011)
Within this paper, we will describe a new approach to customer interaction management by integrating social networking channels into existing business processes. Until now, contact center agents still read these messages and forward them to the persons in charge of customer’s in the company. But with the introduction of Web 2.0 and social networking clients are more likely to communicate with the companies via Facebook and Twitter instead of filling data in contact forms or sending e-mail requests. In order to maintain an active communication with international clients via social media, the multilingual consumer contacts have to be categorized and then automatically assigned to the corresponding business processes (e.g. technicalservice, shipping, marketing, and accounting). This allows the company to follow general trends in customer opinions on the Internet, but also record two-sided communication for customer relationship management.
Keywords: Classification of Multilingual Customer Contacts; Contact Center Application Support; Social Media Business Integration

Towards Multilingual Biographical Event Extraction - Geierhos, Michaela; Bouraoui, Jean-Leon; Watrin, Patrick (Multilingual Resources, Multilingual Applications. Proceedings of the Conference of the German Society for Computational Linguistics and Language Technology (GSCL) 2011)
Within this paper, we describe the special requirements of a semantic annotation scheme used for biographical event extraction in the framework of the Europeancollaborative research project Biographe. This annotationscheme supports interlingual search for people due to its multilingual support covering four languages such as English, German, French and Dutch.
Keywords: Biographical Event Extraction for Interlingual People Search; Semantic Annotation Scheme

Customer Interaction 2.0: Adopting Social Media as Customer Service Channel - Geierhos, Michaela (Journal of Advances in Information Technology)
Since customers first share their problems with a social networking community before directly addressing a company, social networking sites such as Facebook, Twitter, MySpace or Foursquare will be the interface between customer and company. For this reason, it is assumed that social networks will evolve into a common communication channel – not only between individuals but also between customers and companies. However, social networking has not yet been integrated into customer interaction management (CIM) tools. In general, a CIM application is used by the agents in a contact centre while communicating with the customers. Such systems handle communication across multiple different channels, such as e-mail, telephone, Instant Messaging, letter etc. What we do now is to integrate social networking into CIM applications by adding another communication channel. This allows the company to follow general trends in customer opinions on the Internet, but also record two-sided communication for customer service management and the company’s response will be delivered through the customer’s preferred social networking site.
Keywords: Social Media Business Integration; Multichannel Customer Interaction Management; Contact Centre Application Support

Adjective complementation by that-clauses: An empirical study - Mindt, Ilka

Corpus Linguistics and the Description of English - Mindt, Ilka; Lindquist, Hans (ICAME Journal 35)

Anglistische Korpuslinguistik. Eine Einführung. Grundlagen der Anglistik und Amerikanistik 33 - Mindt, Ilka; Mukherjee, Joybrato (Anglistik. International Journal of English Studies, 22, 1)

Introducing Narrative in Drama - Flotmann, Christina; Tönnies, Merle (Narrative in Drama: CDE Studies 18)

Narrative in Drama

Narrative in Drama

Book review: Arthur W. Frank (2010). 'Letting Stories Breathe: A Socio-Narratology.' Chicago: University of Chicago Press - Mildorf, Jarmila (Biography)

BiographIE - Biographical Information Extraction from Business News - Geierhos, Michaela; Blanc, Olivier (Actes du 27e Colloque international sur le lexique et la grammaire (L’Aquila, 10-13 septembre 2008))

BiographIE - Klassifikation und Extraktion karrierespezifischer Informationen - Geierhos, Michaela
Das wesentliche Ziel der vorliegenden Publikation ist die Erstellung von sprachspezifischen Modulen im Bereich der Biographischen InformationsExtraktion (BiographIE). Unter Informationsextraktion verstehen wir die automatisierte Analyse von Dokumenten im Hinblick auf das Entdecken und Normalisieren von semantisch interessanten Entitäten und deren Eigenschaften. Das Hauptgewicht der Arbeit liegt auf sehr detaillierten und umfangreichen linguistischen Grammatiken im Bereich der Beschreibung von Personen und deren Beziehungen zu anderen relevanten Entitäten (z.B. Organisationen, Orte, Datums- und Zeitangaben) in Texten. Neben den öffentlichen und privaten Eigenschaften von Personen (Geburtsdatum, Nationalität etc.) sollen vor allem alle biographisch relevanten Attribute aus Texten extrahiert werden können. Dazu gehören in erster Linie berufliche Werdegänge, Anstellungsverhältnisse, Rollen in Firmen und ähnliche Eigenschaften. Da alle diese Attribute in unzählbar verschiedenen Formen ausgedrückt werden können, müssen sehr umfangreiche Lexika und sehr detaillierte grammatische Beschreibungen erstellt werden. Dies geschieht hauptsächlich bei der systematischen Evaluierung von Korpora. Je umfangreicher diese sind, desto adäquater werden die erstellten Grammatiken sein. Im Gegensatz zu den heute üblichen statistischen, auf maschinellem Lernen basierenden Verfahren setzen wir auch umfangreiche semi-automatisch erstellte, linguistische Module ein, die dann durch systematische Evaluierung auf Korpora schnell ergänzt und verbessert werden können. Basierend auf unseren Extraktionsmethoden ist es nun möglich, im Bereich der semantischen Suche deutliche Fortschritte zu machen. Insbesondere Personensuchmaschinen können sich unsere detaillierten Analysemethoden zu Nutze machen, um beispielsweise zu ermitteln, wer in welcher Funktion bei welcher Firma von wann bis wann beschäftigt war.
Keywords: Natural Language Processing

Beiträge der Sektion I "'Spoken' English through the Centuries." Sprachwissenschaftliche Sektion beim Anglistentag 2009 in Klagenfurt. - Claridge, Claudia; Mindt, Ilka (Anglistentag 2009 Klagenfurt. Proceedings)

Spoken English through the centuries: Introduction - Claridge, Claudia; Mindt, Ilka (Anglistentag 2009 Klagenfurt. Proceedings)

Methoden der Korpuslinguistik: Der korpus-basierte und der korpus-geleitete Ansatz - Mindt, Ilka (Kompendium Korpuslinguistik. Eine Bestandsaufnahme aus deutsch-tschechischer Perspektive)

Reading British Spaces

Das englische Drama der Gegenwart: Kategorien-Entwicklungen-Modellnterpretationen

The Features of Meanings of Orality in Black British Performance Poetry - Tönnies, Merle; Sand, Andrea (Anglistentag 2009 Klagenfurt. Proceedings)

Transgressive Melodrama. The 'Sensational' 1860s and their After-Effects - Tönnies, Merle (Victorian Highways - Victorian Byways. New Approaches to Nineteenth-Century British Literature and Culture)

Negotiating Deviance: Identity, Trajectories and Norms in a Graffitist’s Interview Narrative - Mildorf, Jarmila (Telling Stories: Language, Narrative, and Social Life)

Book review: Franz K. Stanzel. Telegonie -- Fernzeugung: Macht und Magie der Imagination. Wien: Böhlau - Mildorf, Jarmila (Germanisch-Romanische Monatsschrift)

Narratology and the Social Sciences - Mildorf, Jarmila (Postclassical Narratology: Approaches and Analyses)

Business Specific Online Information Extraction from German Websites - Lee, Yeong Su; Geierhos, Michaela (Proceedings of the 9th Dutch-Belgian Information Retrieval Workshop)
This paper presents a system that uses the domain name of a German business website to locate its information pages (e.g. company profile, contact page, imprint) and then identifies business specific information. We therefore concentrate on the extraction of characteristic vocabulary like company names, addresses, contact details, CEOs, etc. Above all, we interpret the HTML structure of documents and analyze some contextual facts to transform the unstructured web pages into structured forms. Our approach is quite robust in variability of the DOM, upgradeable and keeps data up-to-date. The evaluation experiments show high efficiency of information access to the generated data. Hence, the developed technique is adaptive to non-German websites with slight language-specific modifications, and experimental results on real-life websites confirm the feasibility of the approach.
Keywords: company search; information extraction; sublanguage

Key Expression driven Record Mining for Event Calendar Search - Lee, Yeong Su; Geierhos, Michaela (KDML’09 Tagungsband. Workshop-Woche: Lernen - Wissen - Adaptivität. LWA 2009. 21.-23.09.2009)
This paper presents an approach to extract data records from websites, particularly ones with event calendars. We therefore use language-specific key expressions and HTML patterns to recognize every single event given on the investigated web page. One of the most remarkable advantages of our method is that it does not require any additional classification steps based on machine learning algorithms or keyword extraction methods; it is a so-called one-step mining technique. Our experimental results obtained on German opera websites show excellent results in precision and recall. Furthermore, we could demonstrate that our proposed technique outperforms other data record mining applications run on event sites.

Business Specific Online Information Extraction from German Websites - Lee, Yeong Su; Geierhos, Michaela (Computational Linguistics and Intelligent Text Processing: 5th International Conference, CICLing 2004, Seoul, Korea, February 15-21, 2004, Proceedings)
This paper presents a system that uses the domain name of a German business website to locate its information pages (e.g. company profile, contact page, imprint) and then identifies business specific information. We therefore concentrate on the extraction of characteristic vocabulary like company names, addresses, contact details, CEOs, etc. Above all, we interpret the HTML structure of documents and analyze some contextual facts to transform the unstructured web pages into structured forms. Our approach is quite robust in variability of the DOM, upgradeable and keeps data up-to-date. The evaluation experiments show high efficiency of information access to the generated data. Hence, the developed technique is adaptive to non-German websites with slight language-specific modifications, and experimental results on real-life websites confirm the feasibility of the approach.

Guest-editor des Focus On "Corpus Linguistics - Methods and Approaches" - Mindt, Ilka (Anglistik. International Journal of English Studies)

Corpus-based and corpus-driven approaches: An investigation of the verb do - Mindt, Ilka (Anglistik. International Journal of English Studies)

Corpus Linguistics: a discipline on the move - Mindt, Ilka (Anglistik. International Journal of English Studies)

Assmann, A.: Einführung in die Kulturwissenschaft - Tönnies, Merle (Anglistik. International Journal of English Studies)

Lionel Johnson - Flotmann, Christina (Kindlers Literaturlexikon)

Shelagh Delaney 'A Taste of Honey' - Tönnies, Merle (Kindlers Literaturlexikon)

David Hare 'A Map of the World' - Tönnies, Merle (Kindlers Literaturlexikon)

David Hare 'Knuckle' - Tönnies, Merle (Kindlers Literaturlexikon)

David Hare 'Plenty' - Tönnies, Merle (Kindlers Literaturlexikon)

Ann Patricia Jellicoe 'The Knack' - Tönnies, Merle (Kindlers Literaturlexikon)

Stephen Poliakoff 'Strawberry Fields' - Tönnies, Merle (Kindlers Literaturlexikon)

Peter Shaffer 'Amadeus' - Tönnies, Merle (Kindlers Literaturlexikon)

Peter Shaffer 'Equus' - Tönnies, Merle (Kindlers Literaturlexikon)

George Bernard Shaw 'Mrs Warren's Profession' - Tönnies, Merle (Kindlers Literaturlexikon)

Oscar Wilde 'Mrs Henry Wood' - Tönnies, Merle (Kindlers Literaturlexikon)

Mary Elisabeth Braddon 'Lady Audley's Secret' - Tönnies, Merle (Kindlers Literaturlexikon)

Oscar Wilde 'Lady Windermere's Fan' - Tönnies, Merle (Kindlers Literaturlexikon)

Alan Ayckbourn 'Woman in Mind' - Tönnies, Merle (Kindlers Literaturlexikon)

Wilkie Collins 'The Moonstone' - Tönnies, Merle (Kindlers Literaturlexikon)

Oscar Wilde 'East Lynne' - Tönnies, Merle (Kindlers Literaturlexikon)

Book review: Birgit Neumann, Ansgar Nünning and Bo Pettersson (eds) (2008). Narrative and Identity: Theoretical Approaches and Critical Analyses. Trier: Wissenschaftlicher Verlag Trier - Mildorf, Jarmila (Informationsmittel für Bibliotheken)

Book review: Christian Klein and Matías Martínez. (2009) Wirklichkeitserzählungen: Felder, Formen und Funktionen nicht-literarischen Erzählens. Stuttgart: Metzler - Mildorf, Jarmila (Informationsmittel für Bibliotheken)

iBeCOOL - Extraction d'informations biographiques dans les textes financiers - Geierhos, Michaela; Blanc, Olivier; Bsiri, Sandra (Proceedings of the Lexis and Grammar Conference 2008)
Ce papier présente le contexte linguistique et la modélisation de notre système iBeCOOL (Informations Biographiques Extraites à l’aide de COntextes Observés Linguistiquement) dédié à l’extraction d’informations biographiques dans les textes de la presse financière en langue anglaise. La notion d’événement biographique (tel que la naissance, le mariage, la carrière professionnelle) est caractérisée formellement par un schéma prédicatif à plusieurs arguments dont l’un étant une instance de la classe d’objets <Personne>. Notre approche consiste à décrire ces types de relations à l’aide de grammaires locales etde lexiques terminologiques. Nos résultats montrent que cette approche semble viable et nous poussent à élargir cette étude par l’analyse de nouveaux genres textuels.
Keywords: extraction d’informations biographiques; elations sémantiques; grammaires locales; entités nommées; enrichissement du lexique

ProfilPro: Reconstitution automatique d'un profil professionnel à partir des documents du Web - Geierhos, Michaela; Bsiri, Sandra (Linguistics, Computer Science and Language Processing: Festschrift for Franz Guenthner on the Occasion of His 60th Birthday (Tributes 6))

RELAX - Extraction de relations sémantiques dans les contextes biographiques - Geierhos, Michaela; Blanc, Olivier; Bsiri, Sandra (Traitement Automatique des Langues (TAL))

Appropriateness in Discourse: The adjectives surprised and surprising in monologue and dialogue - Mindt, Ilka (Journal of Pragmatics)

Adjective complementation by that-clauses: the relation between the semantics of adjectives and the verb phrase in the that-clause - Mindt, Ilka (Anglistik. International Journal of English Studies)

Progressives, Patterns, Pedagogy. A corpus-driven approach to English progressive forms, functions, contexts and diadactic - Mindt, Ilka; Römer, Ute (Anglistik. International Journal of English Studies, 19, 2)

Corpus Linguistics 25 Years on. (Language and Computers: Studies in Practical Linguistics 62) - Mindt, Ilka; Facchinetti, Roberta (ICAME Journal, Computers in English Linguistics, 2008)

Learning English - the reading performance of a Japanese 'SUE' (successful user of English) - Rumlich, Dominik (Working papers in Applied Linguistics)

Translating African Traditions and Identities. Black Poetry in Contemporary Britain - Tönnies, Merle (Cultures of Translation)

The Visual Strategies of Nineteenth-Century Melodrama - Tönnies, Merle (Anglistik & Englischunterricht 71)

Kulturelle Bedeutungen und Kontexte der indischen Küche in Großbritannien - Tönnies, Merle (Interkulturelle Mahlzeiten. Kulinarische Begegnungen und Kommunikation in der Literatur)

Caselli, D.: Beckett's Dante - Tönnies, Merle (Archiv für das Studium der neueren Sprachen und Literaturen)

The Frontiers of the Sea - Strauß, Sara (Peter Ustinov als Autor – Eine Einführung)

A Nose By Any Other Name - Strauß, Sara (Peter Ustinov als Autor – Eine Einführung)

Structuring Job Search via Local Grammars - Bsiri, Sandra; Geierhos, Michaela; Ringlstetter, Christoph (Research in Computing Science)
The standard approach of job search engines disregards the structural aspect of job announcements in the Web. Bag-of-words indexing leads to a high amount of noise. In this paper we describe a method that uses local grammars to transform unstructured Web pages into structured forms. Evaluation experiments show high efficiency of information access to the generated documents.

Female-on-Male Violence: Medical Responses and Popular Imagination - Mildorf, Jarmila (Gender and Interpersonal Violence: Language, Action and Representation)

Kazuo Ishiguro: Never Let Me Go - Mildorf, Jarmila (Novels. Part II)

Thought Presentation and Constructed Dialogue in Oral Storytelling: Limits and Possibilities of a Cross-Disciplinary Narratology - Mildorf, Jarmila (Partial Answers)

Narrative: Knowing, Living, Telling (Partial Answers)

Grammatik der Menschenbezeichner in biographischen Kontexten - Geierhos, Michaela

Informationsextraktion aus Stellenanzeigen im Internet - Bsiri, Sandra; Geierhos, Michaela (LWA 2007: Lernen - Wissen - Adaption, Halle, September 2007, Workshop Proceedings)
Dieser Beitrag beschäftigt sich mit der Informationsextraktion aus Stellenanzeigen im französischsprachigen Web. Ziel dieser Arbeit ist es, unstrukturierte Dokumente in Repräasentationsvektoren anhand lokaler Grammatiken zu transformieren. Auf diese Weise wird es möglich, den Stellenmarkt für Jobsuchmaschinen transparenter zu gestalten, indem nur auf dem Inhalt der Anzeige in Form von Darstellungsvektoren anstatt auf unübersichtlichem Fließtext gesucht werden muss.

The valency of experiential and evaluative adjectives - Mindt, Ilka (Valency. Theoretical, Descriptive and Cognitive Issues)

Constructing an Emblematic Northern Space. The New Brighton Photographs of Martin Parr and Tom Wood - Tönnies, Merle (Spatial Practices 2)

Stierstorfer, K. / L. Volkmann (Hg.): Kulturwissenschaft Interdisziplinär - Tönnies, Merle (Anglistik. International Journal of English Studies)

Introduction to the Study of British Culture - Tönnies, Merle; Voigt, Ulrich

London-Diversity and Myth - Tönnies, Merle (Viewfinder Special. Lese-und Arbeitsbuch für die gymnasiale Oberstufe)

Storying Domestic Violence: Constructions and Stereotypes of Abuse in the Discourse of General Practitioners - Mildorf, Jarmila

Mad Intertextuality: 'Jane Eyre', 'Wide Sargasso Sea', 'After Mrs Rochester' - Mildorf, Jarmila (A Breath of Fresh Eyre: Intertextual and Intermedial Reworkings of 'Jane Eyre')

Book review: Katharina Uhsadel (2005). Antonia Byatts Quartet in der Tradition des Englischen Bildungsromans. Heidelberg: Winter - Mildorf, Jarmila (Anglistik)

Das Paradigma des Pikaresken - The Paradigm of the Picaresque

Thinking Northern: Textures of Identity in the North of England

Distributional data and grammatical structures: The case of so- called subject extraposition - Mindt, Ilka (Zeitschrift für Anglistik und Amerikanistik 54.2, Special issue on "The scope and Limits of Corpus Linguistics – Empiricism in the Description and Analysis of English)

Forms and Functions of Violence in Contemporary Black British Drama - Tönnies, Merle (Anglistentag 2005)

Foregrounding Boundary Zones. Martin Parr's Photographic (De-)Constructions of Englishness - Tönnies, Merle (Spatial Practices 1)

Percy Mtwa, Mbongeni Ngema and Barney Simon: Woza Albert! (1981) - Tönnies, Merle (Drama II)

New Labour in the New Millenium. A Further Theatricalisation of Politics? - Tönnies, Merle (Passauer Arbeiten zur Literatur-und Kulturwissenschaft)

Radicalising Postmodern Biofictions. British Fictional Autobiography of the Twenty-First Century - Tönnies, Merle (Salzburg Studies in English Literature and Culture)